On Speed and Rotor Position Estimation in Permanent-Magnet AC Drives - Solsona, Jorge Alberto (2000)
This letter deals with rotor position and speed estimation of permanent magnet ac drives. Two reduced-order observers, a linear (AO) and a nonlinear one (NLO), are compared. An adaptive speed estimation scheme is also considered. Analysis and simulations show that the NLO has better performance and demands less computational load than the AO plus the adaptive scheme.